The Northern Experience of Street Involved Youth: A Narrative Inquiry - George, Serena D.; O'Neill, Linda K. (Canadian Journal of Counselling and Psychotherapy, 2011)
This research explored the experiences of 8 street-involved youth (4 male, 4 female) between the ages of 20 and 27 living in north-central British Columbia. The analysis was carried out in 3 phases based on the narrative approach developed by Lieblich, Tuval-Mashiach, and Zilber (1998). The narratives represented the holistic experiences of the youth and the meanings they attached to their experiences. The 26 themes that emerged from the data were organized into 5 main categories representing the participants’ experiences prior to street life, the challenges associated with being on the streets, supports, personal qualities, and moving on. Three overarching metathemes were interpreted from the youths’ narratives: trauma, coping, and the essence of living.